Advances in mixing technology: recent advances in mixing research and development - Hashimoto, S.; Ohmura, N.; Kim, S.J.; Ibrahim, S. (2012)
Mixing has been one of essential unit operations for chemical engineering processes. Among a number of mixers, stirred tanks that are available in a wide variety of tank sizes and impeller shapes are the most frequently adopted to homogenize different substances and to conduct chemical reactions in industrial chemical processes. In addition, there are various technologies for fluid mixing: static mixer, micromixer, unsteady agitation, eccentric agitation, and so on. Recently in various industrial processes, a wide range of operation for stirred tank is required depending on purposes and conditions, and high efficiency on mixing has been strongly required. In addition, the techniques of computer simulation analyses by the use of CFD software have been dramatically developed, which is essential to analyze the mixing mechanism. The main goal of this special issue was to gather contributions dealing with the latest breakthrough of mixing techniques. There is a collection of twelve papers in this special issue focused on mixing fundamental (2 papers), multiphase mixing (3 papers), chemical reactive mixing for metallurgical industry, and biotechnology (4 papers), and new technology of mixing (3 papers) ranging in topic from laminar-to-turbulent mixing by means of both experimental analyses and numerical simulations. The highlights of each paper are introduced as follows.